Cretien van Campen. The Proust Effect – The senses as doorways to lost memories - Westerhof, Gerben; Stevens, Carlijn (Tijdschrift voor Gerontologie en Geriatrie, 2015)
Bespreking: Cretien van Campen. The Proust Effect – The senses as doorways to lost memories. Oxford University Press. ISBN 9870199685875.